Analisis Fundamental Mikro dan Struktur Kepemilikan Terhadap Kinerja Keuangan dengan Struktur Modal, Manajemen Laba, Karateristik Perusahaan sebagai Variabel Intervening pada Perusahaan Perbankan - Atakelan, Reinatto Yakobus Pati Agon; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of the research activity is to determine and analyze the financial performance of banking companies on the Indonesia Stock Exchange from 2013 and 2018. A quantitative descriptive approach is used as a research method for secondary data, respectively for each independent and dependent variable. Where the independent variables are: Micro fundamentals, Ownership Structure, Capital Structure, Profit Management, Company Characteristics, and the dependent variable is: Financial Performance. Data is taken from financial reports and also the IDX website (www.idx.co.id). Banking companies on the IDX were involved in this research from 2013 to 2018. A sample of 5 banking companies was taken for analysis, using random sampling. From the results of the analysis, there is only one independent variable that has a significant effect on the dependent variable, and the remaining independent variables do not have a significant effect on financial performance.